Ikhtiyaroot Sayyid Sabiq Al-Fiqiyyah Fii Buyu' - Kurniawan Pasmadi, Achmad (2011)
Fiqih Sunnah is one of the fiqih's books which is a famous book, recently the book is used for many Islamic countries, it has a special thing for people who want to know a real book of Fiqih that's not fanaticize to one of the four madzhabs and does't injure one of the four madzhabs. But many people whom imitative to one of the four madzhabs criticize this book, and most of them tell that book invite moslem to leave the madzhab, and than there are many ulama criticize and said that sayid sabiq was left the madzhabs, and his book doesn't give a real position for study of analogy and study of balance, when discussing about argumentations from brains and from relevation, and balancing study both of them, and chooses more probable one of any opinion, by the right method. From two motive ago, the researcher of this thesis want to research fiqih sunnah sayid sabiq to answer back any complain from ulama to this book. By the title "Sayid Sabiq Selections Of Fiqih At Trading Chapter" and the motive of bounded research At Trade Chapter is to centralization object of research and because the trading chapter is the real importent thing between moslems and because the problem of trading chapter progress every day with necessity of people, and than need to answer and give solutions with the right method. To the debunk of this problem, the researcher takes three questions of the research :the first, what are sayid sabiq selections of fiqih at trading chapter? The second, what are sayid sabiq probability methods in fiqih sunnah At Trading chapter? The third, what are the overpluses and the a shortage of sayid sabiq probability methods in fiqih sunnah At Trading Chapter? And the researcher of this thesis uses references research to research this thesis. and uses two methods there are, comparison method: this methode is used to descrip and to compare sayid sabiq opinions with the four madzhabs to know the agreement and the defference between them. analytical method: this method to analys fidelity what the madzhab sayid sadiq takes his opinion from kind transactions of Trade Chapter. which sayid sabiq position in the four madzahibs does his opinions chooses from one of the four madzhabs? Or does he chooses to research the right opinion between the four madzhabs? Or does he only takes his opinions of one madzhab from the four madzhabs without research the right opinion by the method?. The results of this study is sayid sabiq in the 17 kinds of transactions of trading in fiqih sunnah, sayid sabiq in the some transactions chooses the opinion from specific madzhab. And sometimes he takes the opinion from specific madzhab with his opinion, and this is little. And he discript some transactions and does not chooses one of dissenting opinion, and sayid sabiq leaves the reader of fiqih sunnah who ask anotherone who knows the right answer. And the recapitulation is sayid sabiq choses his best opinion